(untitled) (Bangladesh Journal of Medical Science, 2013)
Calcifying epithelial odontogenic tumor is a rare benign epithelial odontogenic lesion that comprises from 0.2% to 1.1 of all odontogenic tumors. In the past a number of different names have been given to this lesion, such as calcifying ameloblastoma, cystic complex odontoma, uncommon ameloblastoma with calcifications and others. There is a need to study and explore various aspects of this tumour, this article gives a broad idea of the various aspects of this tumor and which aspect of this tumour needs more investigation. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17378 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 14-19